Hyaluronan- and heparin-reduced silver nanoparticles with antimicrobial properties. (June 2009) - Kemp, Melissa M; Kumar, Ashavani; Clement, Dylan; Ajayan, Pulickel; Mousa, Shaker; Linhardt, Robert J
Aims: Silver nanoparticles exhibit unique antibacterial properties that make these ideal candidates for biological and medical applications. We utilized a clean method involving a single synthetic step to prepare silver nanoparticles that exhibit antimicrobial activity. Materials & methods: These nanoparticles were prepared by reducing silver nitrate with diaminopyridinylated heparin (DAPHP) and hyaluronan (HA) polysaccharides and tested for their efficacy in inhibiting microbial growth. Results & discussion: The resulting silver nanoparticles exhibit potent antimicrobial activity against Staphylococcus aureus and modest activity against Escherichia coli . Silver––HA showed greater antimicrobial activity than silver––DAPHP, while silver––glucose nanoparticles exhibited very weak antimicrobial activity. Neither HA nor DAPHP showed activity against S. aureus or E. coli .Conclusion: These results suggest that DAPHP and HA silver nanoparticles have potential in antimicrobial therapeutic applications.